Country Partnership Framework for the United Republic of Tanzania for the Period FY18-FY22 - World Bank Group (World Bank, Washington, DC, 2018)
The Country Partnership Framework (CPF) for Tanzania covering FY18-FY22 comes at a time when Tanzania must both consolidate the gains of the last decade and address the continuing gaps in its development outcomes—including sharp spatial (rural-urban) and gender disparities in income and assets, continued challenges with respect to human capital and delivery of public services, and unsustainable use of critical natural resources. To address this, Tanzania has set out an ambitious agenda of nurturing industrialization for economic transformation, and human development. The CPF supports this agenda which is laid out in Tanzania’s Second Five-Year Development Plan (FYDP II) and Zanzibar’s Third Strategy for Growth and Reduction of Poverty (ZSGRP III). The Systematic Country Diagnostic (SCD) for Tanzania identifies three pathways to leverage the country’s advantages to achieve the national development goals: (i) structural transformation to leverage Tanzania’s natural assets and capture latent comparative advantage to create more jobs; (ii) spatial transformation to build on Tanzania’s geographic advantages and maximize benefits from spatial integration and agglomeration; and (iii) upgrading public institutions and organizations, underpinned by expanding human capital, gender equity, and macroeconomic stability. Following a decade of strong growth and poverty reduction, the CPF addresses the challenges of carving a growth path that is more inclusive and sustainable.The CPF recognizes the close nexus between climate change and poverty reduction in Tanzania and places a strong emphasis on addressing the effects of climate change. The CPF will call upon the full range of World Bank Group (WBG) instruments and financial products to respond to Tanzania’s needs. The CPF will address International Development Association (IDA) special themes and seek to be agile in preparing operations and analytical products. The CPF program has three areas of strategic focus. The Focus Area 1, enhance productivity and accelerate equitable and sustainable growth—is closely aligned with the FYDP II’s emphasis on industrialization, and with the SCD structural and spatial transformation pathways for development. The SCD’s first foundation, macroeconomic stability, is necessary for creating a conducive environment for private investment and growth. Focus Area 2, boost human capital and social inclusion—is aligned with the human development pillar of the FYDP II and the SCD’s second foundation, human development and gender equity. Focus Area 3, modernize and improve efficiency of public institutions—is aligned with the SCD’s emphasis on institutional transformation and the Tanzanian Government’s priority on public sector accountability, private sector support and regulation, and capacity to deliver services. The three CPF focus areas are not mutually exclusive and can be leveraged to achieve substantial progress on overlapping goals. For example, if workers acquire job-relevant skills (Focus Area 2), that will contribute to the job creation goal (Focus Area 1); and improving accountability and PFM is fundamental to reaching service delivery objectives for health and education (Focus Area 3). Similarly, expanding social inclusion requires action in all focus areas.